CONSUMER CHARACTERISTICS AND FACTORS THAT INFLUENCE CONSUMER DECISIONS AT KOPIXEL IN JEMBER REGENCY - Retalia Risma Sari (Universitas Tulungagung, 2025)
This study is motivated by the rise of coffee shops as part of a growing co fee consumption Lifestyle trend. In Jember Regency, Kopixel stands out as the most favored co fee shop among consumers. The objectives of this research are to identify: (1) the characteristics of Kopixel consumers and (2) the factors influencing their purchasing decisions. The study uses a descriptive-analytic method, with data collected through interviews and documentation. Analysis techniques include descriptive statistics and multiple linear regression. The results show that Kopixel consumers are 51.04% female and 48.96% male, with the majority aged 20-24 (63.54%) and earning over IDR 4,000,000 (21.88%). Most drink ccjfee 2-3 times a week (44.79%) but rarely visit Kcpixel (33.33%). Arabica is preferred (67%), with Kopixel late as the favorite variant (24.21%). The main reason for visiting is socializing with friends (37.50%), with typical spending of IDR 25,000-40,000 (32.29%). Six factors influence purchase decisions: Product, Place, Promotion, People, Process, and Physical Evidence. The results highlight the importance of product innovation, service quality, and atmosphere in shaping consumer behavior and sustaining competitiveness in the dynamic coffee shop industry.